Service life prediction for concrete structures based on carbonation front depth models - Pinto Costa, Rayara; Simas Franchetto, Alessandro; Smolinski Gouveia, Ana Jújlia; Ziegler, Fabiana; Queiros Pessoa, Kennedy; Garcez, Mónica Regina (Revista ALCONPAT, 2022)
This paper seeks to evaluate the variability in predicting the service life of concrete structures through four models that estimate the natural advance of the carbonation front. The results show that there is variability in the estimated carbonation front. The models by Possan (2010) and Ekolu (2018) show estimated values close to measured ones, while Ho and Lewis (1987) and Bob and Affana (1993) tend to underestimate and overestimate the natural carbonation front, respectively. Only concretes without added supplementary cementitious materials were considered, due to model limitations. Compressive strength, CO2 concentration and relative humidity have significant influence on the results and the variability depends on which parameters are considered in the models.